Electrical transport properties of Ge-doped GaN nanowires. (11th March 2015) - Schäfer, M; Günther, M; Länger, C; Müßener, J; Feneberg, M; Uredat, P; Elm, M T; Hille, P; Schörmann, J; Teubert, J; Henning, T; Klar, P J; et al.
Abstract: The conductivity and charge carrier concentration of single GaN nanowires (NWs) doped with different concentrations of Ge were determined by four-point resistivity and temperature-dependent Seebeck coefficient measurements. We observed high carrier concentrations ranging from 9.1 × 10 18 to 5.5 × 10 19 cm −3, well above the Mott density of 1.6 × 10 18 cm −3, and conductivities up to 625 S cm −1 almost independent of the NW diameter. The weak temperature dependence of the conductivity between 2 and 10 K could be assigned to the formation of an impurity band. For the sample with the highest conductivity metallic behaviour was found, indicated by a positive temperature coefficient of the resistivity. The near band edge emission analyzed by micro-photoluminescence spectroscopy showed only a small increase of the peak width up to 70 meV and no spectral shift for carrier concentrations up to 5.5 × 10 19 cm −3 . The latter was attributed to the simultaneous influence of band filling, band gap renormalization, and strain.